Collaborating with Students to Create Law Assessment: A Case Study - Alex Deagon (Bond Law Review)
Many students are driven by their perceptions of assessment, and consequently, assessment can be used as a tool to enhance the learning process. The increased focus on student-centred learning in this context has resulted in student involvement in assessment. However, the literature in law focuses primarily on self-assessment and peer assessment, or criteria and marking, rather than student involvement in the creation of assessment content. This article investigates collaborative assessment in the context of legal education by undertaking a case study of staff collaborating with students to create the content of assessment in the undergraduate law subject ‘Evidence’ at the Queensland University of Technology. The case study found through surveys that when students have a degree of choice in the creation of assessment, they feel more confident, engaged and motivated to complete the assessment. Students felt this enhanced their learning experience. This study adds to the literature on student involvement in assessment by specifically considering collaborative assessment in law, which can then inform teaching practices with the aim of enhancing the learning experience for students.